The Effect of Work Stress, Job Satisfaction, and Organizational Climate on Turnover Intention (Survey on Employees of PT Allied Industrial Indonesia) - Dede Jaelani; Rika Desiani (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Achmad Yani, 2020)
Abstract The purpose of this study was to determine the description of Job Stress, Job Satisfaction, Organizational Climate and Turnover Intention at PT. Allied Industrial Indonesia, to find out how the Effect of Job Stress, Job Satisfaction, and Organizational Climate on Turnover Intention of PT. Allied Industrial Indonesia simultaneously, to determine the Effect of Job Stress on Turnover Intention of PT. Allied Industrial Indonesia, to determine the Effect of Job Satisfaction on Turnover Intention of PT. Allied Industrial Indonesia, to determine the Influence of Organizational Climate on Turnover Intention of PT. Allied Industrial Indonesia. The results of the discussion show that the statistical hypothesis testing results indicate that overall, there is a significant influence between Job Stress, Job Satisfaction, and Organizational Climate on Turnover Intention. Individual test results also show that the variables of Job Stress and Organizational Climate have a significant effect on Turnover Intention, while the Job Satisfaction variable has no significant effect. The conclusion of this study is that there is a positive and significant effect of Job Stress on Turnover Intention at PT. Allied Industrial Indonesia, meaning that the higher the Work Stress, the higher the Turnover Intention. There is a negative and insignificant effect of Job Satisfaction on Turnover Intention, meaning that the higher the Job Satisfaction, the lower the Turnover Intention. There is a negative and significant influence of Organizational Climate on Turnover Intention, meaning that the better the Organizational Climate, the lower the Turnover Intention. Abstrak Tujuan Penelitian ini adalah untuk mengetahui gambaran Stres Kerja, Kepuasan Kerja, Iklim Organisasi dan Turnover Intention pada PT. Allied Industrial Indonesia, untuk mengetahui bagaimana Pengaruh Stres Kerja, Kepuasan Kerja, dan Iklim Organisasi Terhadap Turnover Intention PT. Allied Industrial Indonesia secara simultan, untuk mengetahui Pengaruh Stres Kerja Terhadap Turnover Intention PT. Allied Industrial Indonesia, untuk mengetahui Pengaruh Kepuasan Kerja Terhadap Turnover Intention PT. Allied Industrial Indonesia, untuk mengetahui Pengaruh Iklim Organisasi Terhadap Turnover Intention PT. Allied Industrial Indonesia. Hasil pembahasan diketahui bahwa hasil pengujian hipotesis statistik ini menunjukkan bahwa secara keseluruhan terdapat pengaruh signifikan antara Stres Kerja, Kepuasan Kerja, dan Iklim Organiasasi terhadap Turnover Intention. Hasil pengujian secara individu dapat diketahui pula bahwa variabel Stres Kerja dan Iklim Organisasi berpengaruh signifikan terhadap Turnover Intention, sedangkan variabel Kepuasan Kerja tidak berpengaruh signifikan. Kesimpulan dari penelitian ini adalah terdapat pengaruh yang positif dan signifikan dari Stres Kerja terhadap Turnover Intention pada PT. Allied Industrial Indonesia, artinya semakin tinggi Stres Kerja maka semakin tinggi Turnover Intention. Terdapat pengaruh yang negatif dan tidak signifikan dari Kepuasan kerja terhadap Turnover Intention, artinya semakin tinggi Kepuasan Kerja maka semakin rendah Turnover Intention. Terdapat pengaruh yang negatif dan signifikan dari Iklim Organisasi terhadap Turnover Intention, artinya semakin baik Iklim Organisasi maka semakin rendah Turnover Intention.